Q. 2 I4.3( 3 Votes )

# Solve the followi

Answer :

Cross Multiplying in the above equation,

(x + 3) × (2x – 3) = (3x – 7) × (x + 2)

2x2 – 3x + 6x – 9 = 3x2 + 6x – 7x – 14

2x2 + 3x – 9 = 3x2 – x – 14

3x2 – 2x2 – x - 3x – 14 + 9 = 0

x2 - 4x – 5 = 0

On factorizing the above equation,

x2 + x – 5x – 5 = 0

x(x + 1) – 5(x + 1) = 0

(x – 5) (x + 1) = 0

Solving the first part,

x – 5 = 0

x = 5

Solving the second part,

x + 1 = 0

x = -1

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

If u(x) = (x – 1)Rajasthan Board Mathematics

Find the lowest cRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

The area of a recRajasthan Board Mathematics

The LCM and HCF oRajasthan Board Mathematics

If α and β are thRajasthan Board Mathematics

Find the zeroes oRajasthan Board Mathematics

Write ShridharachRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics